Anesthesia outside the Operating Room in a Patient with Mitochondrial Disease. (16th May 2020) - Fadrique-Fuentes, Alejandra; Martínez-Rafael, Beatriz; Poves-Álvarez, Rodrigo; Gómez-Pesquera, Estefanía
Abstract : Mitochondrial dysfunction comprehends a wide range of genetic disorders. These patients' precarious metabolic balance makes its management difficult. Furthermore, the same systems affected by mitochondrial disease can be altered by many of the frequently used anesthetic agents. Each patient has to be evaluated individually according to their comorbidities and anesthetic requirements.